Ideološko zaznamovana recepcija Steinbeckovih del v komunistični Vzhodni Evropi - Čerče, Danica (Jezik in slovstvo, 2018)
Despite some differences between the ruling regimes in the countries of the former communist Europe, the critical reception of Steinbeck and his works in these countries shares several commonalities. The social and economic environment of one-dimensional ideological views, in which literary works were mainly assessed from the perspective of sociological discourse and evaluated on the basis of their political correctness, created an idealised perception of the writer, with his/her works being praised as exemplary of the role of literature in attaining political aims. The similarities in Steinbeck's status in these countries are also evident after their transition to democracy. Following the decrease in the ideological manipulation of literature with the concomitant emphasis on its aesthetic conceptualisation, the whole region has experienced increased interest of translators and publishers in Steinbeck's lesser-known works, which were previously marginalised due to their lack of ideological structures.
Keywords: ameriška književnost; ideološko zlorabljanje književnosti; komunizem; mitizirana podoba pisatelja; Steinbeck, John; Vzhodna Evropa